A low-carbohydrate dietary pattern characterised by high animal fat and protein during the first trimester is associated with an increased risk of gestational diabetes mellitus in Chinese women: a prospective cohort study. Issue 12 (28th December 2021) - Dong, Hongli; Sun, Hong; Cai, Congjie; Pang, Xinxin; Bai, Dan; Lan, Xi; Zhang, Yiqi; Zhang, Ju; Zeng, Guo
Abstract: We aimed to examine the association between low-carbohydrate diet (LCD) scores during the first trimester and gestational diabetes mellitus (GDM) risk in a Chinese population. A total of 1455 women were included in 2017. Dietary information during the first trimester was collected by 24-h dietary recalls for 3 d. The overall, animal and plant LCD scores, which indicated adherence to different low-carbohydrate dietary patterns, were calculated. GDM was diagnosed based on the results of a 75-g, 2-h oral glucose tolerance test at 24–28 weeks gestation. Log-binomial models were used to estimate relative risks (RR) and 95 % CI. The results showed that the multivariable-adjusted RR of GDM from the lowest to the highest quartiles of the overall LCD score were 1·00 (reference), 1·15 (95 % CI 0·92, 1·42), 1·30 (95 % CI 1·06, 1·60) and 1·24 (95 % CI 1·01, 1·52) ( P = 0·026 for trend). Multivariable-adjusted RR (95 % CI) of GDM from the lowest to the highest quartiles of the animal LCD score were 1·00 (reference), 1·20 (95 % CI 0·96, 1·50), 1·41 (95 % CI 1·14, 1·73) and 1·29 (95 % CI 1·04, 1·59) ( P = 0·002 for trend). After additional adjustment for gestational weight gain before GDM diagnosis, the association of the overall LCD score with GDM risk was non-significant, while the association of animal LCD score with GDM risk remained significant. In conclusion, a low-carbohydrate dietary pattern characterised by high animal fat and protein during the first trimester is associated with an increased risk of GDM in Chinese women.